Analisa Pengaruh Variasi Pengelasan Tungsten Inert Gas (TIG) terhadap Sifat Material Aisi 304 pada Sudu Runner Turbin Francis - Ali Ali; Diaz Waluya Pratama (Pusat riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of Tungsten Inert Gas (TIG) welding parameter variations on the mechanical and metallurgical properties of AISI 304 austenitic stainless steel, which is widely used in construction and industrial applications due to its excellent corrosion resistance and joint strength. The research focuses on identifying the optimal welding current to minimize welding defects and enhance joint structural integrity. Welding current was varied at three levels, namely 100 A, 125 A, and 135 A, while other parameters such as welding speed, argon shielding gas flow rate, and electrode type were kept constant. Mechanical properties were evaluated through Micro-Vickers hardness testing conducted in the weld metal, Heat Affected Zone (HAZ), and base metal, as well as tensile testing to determine ultimate tensile strength and elongation. In addition, non-destructive testing using the dye penetrant method was performed to detect surface welding discontinuities. Metallographic analysis was carried out using optical microscopy following an etching process to observe grain morphology, grain size, and the formation of microstructural phases. The results are expected to demonstrate a correlation between increased heat input due to higher welding current and changes in mechanical properties and microstructure, particularly in the HAZ. This study provides practical guidance for determining optimal TIG welding parameters for AISI 304 to achieve high tensile strength, homogeneous hardness distribution, and a stable microstructure resistant to intergranular corrosion.